Towards a process model of supervision in social work– a bibliometric analysis - Vîșcu, Loredana-Ileana; Rad, Dana (Technium Education and Humanities, 2024)
Supervision plays a pivotal role in social work, ensuring ethical practices, professional growth, and the delivery of quality services. This study conducts a bibliometric analysis to explore the evolving conceptualizations and applications of supervision in social work. Using the Web of Science Core Collection, a search for studies with "supervision AND social work" in their titles yielded 246 works. Full bibliographic records were downloaded and analyzed using VOSviewer software. A co-occurrence analysis of all keywords, with a minimum occurrence threshold of one, identified 89 keywords relevant to the topic. Excluded terms included regional and cultural-specific terms such as "England," "Ontario," and "Maori concepts," to maintain a focused and universal scope. The analysis revealed several thematic clusters encompassing clinical supervision, external supervision, crisis management, and child welfare supervision, among others. Notable themes include the intersection of supervision with burnout, cultural competence, and outcomes, highlighting its complex nature. The study emphasizes the significance of supervision frameworks tailored to diverse contexts and professional roles within social work. The findings contribute to the development of a process model for supervision, offering insights for researchers, educators, and practitioners to enhance supervisory practices. By identifying critical trends and gaps, this bibliometric analysis provides a foundation for future investigations aimed at refining supervision processes in social work.